Numerical simulation of stabilisation of floating wind with submerged hydrofoil - Wang, Junxian; Yang, Liang; Xing, Jingru; Yang, Jianhui (IOP Publishing, 2024)
This research focuses on the optimal design and method of attaching a submerged hydrofoil to an offshore platform to enhance stabilisation. The flapping hydrofoil, exhibiting a hybrid motion combining heave and pitch, is engineered to convert incoming wave energy. It generates a distinctive wake that effectively counteracts incoming waves, thereby reducing wave impact. In this study, a NACA0030-type hydrofoil was strategically positioned between two columns of the platform model. Comprehensive analyses were conducted to evaluate the free-floating platform's response to regular waves, with a focus on the attached hydrofoil. The results indicate that the hydrofoil significantly reduces the surge motion and drifting speed of the platform, affirming its effectiveness in enhancing stabilisation.
In: The Science of Making Torque from Wind (TORQUE 2024) 29/05/2024 - 31/05/2024 Florence, Italy